Socialization of Business Registration Number and Empowerment of MSMEs in Villages Metatu - Nickko Ronaldo, Marcellino; Adi Septa, Anggardha (Kontribusia : Research Dissemination for Community Development, 2024)
Metatu Village is one of the villages in Benjeng sub-district, Regency Gresik. The majority of the population is engaged in MSMEs, there are problems with several actors MSMEs do not yet have a business identification number or NIB. Besides that MSME products Still marketed with method traditional as well as para perpetrator MSMEs Not yet apply report simple finances. From this problem, immediately identify the problem through survey, interview, socialization And discussion with give understanding about legality in try, give education And solution about technical marketing as well as give education about making report finance simple in try. Results Which in achieved namely that MSME players understand the procedures for making NIB, implementing product branding for use increase sale as well as increasing understanding perpetrator MSMEs about making report finance simple in try through program devotion public held in the form of socialization to para perpetrator MSMEs in the village Metatu.